Assessing the Biochar Effects on Selected Physical Properties of a Sandy Soil: An Analytical Approach. Issue 12 (4th July 2017) - Dokoohaki, Hamze; Miguez, Fernando E.; Laird, David; Horton, Robert; Basso, Andres S.
ABSTRACT: Biochar application to soils is a promising practice with agronomic and environmental benefits. Our analysis is based on an experiment in which soil columns were incubated with three biochar application rates (0%, 3% and 6% w/w), two application methods and three replications. Soil water retention curves (SWRCs) were determined at three sampling times, 15, 29 and 91 days, after the start of the incubation. The van Genuchten (VG) model was fitted to all SWRCs and then used to estimate the pore-size distribution (PSD). Standard deviation (SD), skewness and mode (D) were calculated to interpret the geometry of PSDs. The Dexter "S-index" and saturated hydraulic conductivity (Ks ) were also estimated using the VG model parameters. Statistical analysis was performed for all the parameters using a linear mixed model. Relative to controls, all biochar treatments showed increased porosity, water content at both saturation and field capacity and improved soil physical quality. Biochar applications lowered, Ks, bulk density and D, indicative of a shift in PSDs toward smaller pore sizes.